A constitutive model of cyclic plasticity with Lode dependence for structural steels. (August 2022) - Yao, Zucheng; Wang, Wei; Kanvinde, Amit
Highlights: A new constitutive model of cyclic plasticity is proposed for structural steels. Both isotropic hardening and kinematic hardening are considered in the plasticity theory. The isotropic hardening is modified with Lode dependence, and constrained with a memory surface. A non-associative plastic flow rule is applied. A series of mathematical derivations are conducted for the numerical implementation. Uniaxial and shear specimens are tested under monotonic and cyclic loadings for the calibration and verification. Abstract: A finite strain constitutive model is proposed to represent the cyclic elastoplastic response of structural steels. The model simulates the Lode angle dependence of plastic response, which has been recently observed in experimental studies. The model combines Frederick-Armstrong kinematic hardening rules with an exponential isotropic hardening rule, and a non-associated plastic flow rule. A Lode angle-dependent coefficient is defined to modify the isotropic hardening response and determine the shape of yield surface, with respect to the conventional von Mises surface. Stabilization of hysteresis for cyclic plasticity is achieved through a memory surface, defined in the plastic strain space. Analytical formulas for an implicit Return-Mapping algorithm are derived to realize the numerical implementation of this model via a UMAT user subroutine. The effect of Lode dependence of the plasticity response of structural steel Q235 is investigated through monotonic and cyclic experiments on flat shear specimens. A process for parameter identification is outlined, and model predictions are validated through comparison with experimentally-measured force–displacement curves on uniaxial and shear specimens.